(untitled) (Shahroud Journal of Medical Sciences, 2021)
Background: This study aimed to determine the mediating role of distress tolerance in the relationship between early maladaptive schemas and psychiatric symptoms among addicts. Methods: The statistical population of this study consists of addicts referring to addiction treatment clinics in Zanjan city, Iran. Using the multi-stage cluster sampling method, 150 participants were selected as a sample and completed the questionnaires. Early maladaptive schema questionnaire-short form, symptom checklist-25 (SCL-25), and the distress tolerance scale were completed by participants. Results: The findings of this study indicate a negative and significant relationship between early maladaptive schemas and distress tolerance among addicts. Also, there is a positive and significant relationship between early maladaptive schemas and psychiatric symptoms among addicts. It can be said that there is a significant negative relationship between distress tolerance and psychiatric symptoms in addicts. Conclusions: The final results of this study show that in the relationship between early maladaptive schemas and psychiatric symptoms among addicts in Zanjan city, distress tolerance plays a mediating role and the model has a goodness of fit. Keywords: Distress tolerance, Early maladaptive schemas, Psychiatric symptoms, Addicts.